(untitled) (Journal of Parents and Teachers, 1995)
The importance of children’s literature in education is discussed, especially in the exploration of themes such as fear. The collaboration between municipalities and schools to enrich the education of young people is emphasized. In addition, the role of municipal libraries and literary events in the promotion of reading is highlighted.